Reformulation of the Existence of the Death Penalty Based on the 2023 Criminal Code - Manurung, Abraham Hadonganan; Waluyo, Bambang (UNIVERSITAS PAKUAN, 2025)
AbstractThe death penalty reform in Indonesia’s Criminal Code (KUHP) 2023 marks a transition from a repressive penal system to a more humanistic approach. Under the previous code, capital punishment was a principal and final sentence, whereas the 2023 KUHP redefines it as an alternative punishment with a ten-year probation period. This study aims to assess the effectiveness of this reform and the need for a new implementing law. Using a normative juridical method with statutory and comparative approaches, data were collected through literature research and analyzed qualitatively. The findings show that the implementation of the death penalty still relies on Law No. 2 of 1964, which no longer reflects the humanitarian spirit of the new KUHP. Therefore, a new implementing law is needed, as mandated by Article 102 of the KUHP, to regulate lethal injection, establish a Medical Execution Unit, and provide ethical guidelines for doctors to ensure executions are conducted professionally and in line with human rights principles. Keywords: Death Penalty, Criminal Law Reform, Lethal Injection, Human Rights.